Environmentally-Friendly Synthesis of Carbonate-Type Macrodiols and Preparation of Transparent Self-Healable Thermoplastic Polyurethanes - Kim, Seon-Mi (Polymers (Basel), 2017)
Carbonate-type macrodiols synthesized by base-catalyzed polycondensation of co-diols and dimethyl carbonate as an environmentally-friendly route were subsequently utilized for the preparation of transparent and self-healable thermoplastic polyurethanes (TPUs) containing a carbonate-type soft segment. Three types of macrodiols, obtained from mono, dual and triple diol-monomers for target molecular weights of 1 and 1.5 kg mol(−1), were analyzed by (1)H NMR integration and the OH titration value. Colorless transparent macrodiols in a liquid state at a room temperature of 20 °C were obtained, except the macrodiol from mono 1,6-hexanediol. Before TPU synthesis, macrodiols require pH neutralization to prevent gelation. TPUs synthesized by a solution pre-polymer method with 4,4′-methylene(bisphenyl isocyanate) and 1,4-butanediol as a chain extender exhibited moderate molecular weights, good transparencies and robust mechanical properties. Especially, the incorporation of 3-methyl-1,5-pentanediol within carbonate-type macrodiols enhanced the transparency of the resultant TPUs by decreasing the degree of microphase separation evidenced by ATR-FTIR and DSC. Interestingly, packing density of hard segments and the degree of microphase separation determined the self-healing efficiency of TPUs, which showed good performances in the case of sourced macrodiols from triple diol-monomers.